Severe Pulmonary Infection in a 20-Month-Old Female - Yasmeen Mann; Paul Zeller; Kristen Carrillo-Kappus; Melissa Victor; Mary Moore (Case Reports in Infectious Diseases)
Community-Acquired Pneumonia (CAP) is a common reason for hospitalization of a pediatric patient. We report a 20-month-old female admitted for suspected CAP. History included a week-long cough, fever, dyspnea, single occurrence of seizure-like activity, and a sick contact. Initial chest X-ray (CXR) showed left lower lobe pneumonia and parapneumonic effusion with a complex left pleural effusion. Ultrasound findings prompted the need for contrast-enhanced computed tomography (CT) of the chest. Contrast-enhanced CT of the chest confirmed a large pleural effusion with major atelectasis and mediastinal shift. The patient was treated with empiric antibiotics, video-assisted thoracoscopic surgical (VATS) decortication of empyema, and chest tube placement. Due to intraoperative complications, the VATS decortication was aborted and patient was transferred to the pediatric intensive care unit (PICU). A thoracentesis with culture failed to isolate a bacterial organism. Dexamethasone was started after repeat CXR showed persistent infiltrate. Subsequent contrast-enhanced CT of the chest showed a large collection of air and persistent consolidation. The patient received repeat VATS decortication and reinsertion of a chest tube. Repeat pleural fluid cultures failed to isolate a bacterial organism. Infectious disease (ID) consult recommended linezolid 140 mg Q8H for 4 weeks. Seven days after second VATS, a respiratory pathogen panel was positive for rhinovirus/enterovirus. With resolution of leukocytosis and clinical improvement, the patient was discharged with the chest tube in place and pediatric surgery outpatient follow-up. After three months, sequalae from both the infection and interventions presented .